Nursing workloads in family health: implications for universal access - Denise Elvira Pires de Pires; Rosani Ramos Machado; Jacks Soratto; Magda dos Anjos Scherer; Ana Sofia Resque Gonçalves; Letícia Lima Trindade (Universidade de São Paulo, 2016)
Objective to identify the workloads of nursing professionals of the Family Health Strategy, considering its implications for the effectiveness of universal access. Method qualitative study with nursing professionals of the Family Health Strategy of the South, Central West and North regions of Brazil, using methodological triangulation. For the analysis, resources of the Atlas.ti software and Thematic Content Analysis were associated; and the data were interpreted based on the labor process and workloads as theorical approaches. Results the way of working in the Family Health Strategy has predominantly resulted in an increase in the workloads of the nursing professionals, with emphasis on the work overload, excess of demand, problems in the physical infrastructure of the units and failures in the care network, which hinders its effectiveness as a preferred strategy to achieve universal access to health. On the other hand, teamwork, affinity for the work performed, bond with the user, and effectiveness of the assistance contributed to reduce their workloads. Conclusions investments on elements that reduce the nursing workloads, such as changes in working conditions and management, can contribute to the effectiveness of the Family Health Strategy and achieving the goal of universal access to health.